KURS DAN VALUTA ASING DALAM SISTEM PEREKONOMIAN TERBUKA: TINJAUAN KONSEPTUAL ATAS FAKTOR-FAKTOR YANG MEMENGARUHI NILAI TUKAR DAN VOLATILITASNYA - Bangun, Dian Eka Matra Putra; Remus Silalahi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Economic globalization has significantly driven the increase in international trade activities, cross-border investments, and global capital flows, making exchange rates and foreign currency crucial elements in an open economy. This study aims to comprehensively examine the concept of exchange rates and foreign currency, their strategic role in the global economy, and the factors influencing exchange rate movements and volatility. The method employed in this study is a descriptive-qualitative approach through a literature review of macroeconomic theories, foreign exchange markets, exchange rate systems, and exchange rate risk management practices. The findings indicate that exchange rates not only function as a medium of currency exchange but also reflect fundamental economic strength, monetary stability, and market participants' expectations regarding a country's prospects. Foreign currency plays an important role in facilitating international trade, investment, and global economic integration; however, high exchange rate fluctuations have the potential to create economic risks, particularly for developing countries. Exchange rate volatility is influenced by fundamental and technical factors, including inflation, interest rates, national income, government policies, and market speculation. This study confirms that exchange rate management and foreign exchange risk mitigation are strategic necessities for governments, businesses, and financial institutions to maintain economic stability and enhance national competitiveness in facing the dynamics of the global economy.